(untitled) (Revista Contexto & Saúde, 2023)
The aim of this study was to identify the prevalence and factors associated with alcohol consumption. Cross-sectional study with 3620 adolescents from public and private schools in Porto Velho (RO), 2018. Poisson regression was performed to calculate the prevalence ratios. The prevalence of alcohol consumption was 22.2%, and the alcoholic beverage with the highest preference to beat (cachaça+vodka/cognac) 37.1%. They start consuming alcohol around 12 years. Higher alcohol consumption was associated with male risk factors (p=0.009), 14 years or more (p<0.001), private school (p=0.009), high school (p=0.010), physically active (p=0.040), two-hour mis connected to social networks (p<0.001), overweight (p=0.040) and negative health perception (p<0.001). Alcohol consumption among adolescents was high. These epidemiological findings may contribute to the implementation of public policies in schools in the control and orientation of access to alcoholic beverages.